1987
DOI: 10.1530/jrf.0.0810501
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy resulting from cattle oocytes matured and fertilized in vitro

Abstract: Follicular oocytes (n = 81) collected from cattle at a local slaughterhouse were matured and fertilized in vitro. Of 27 ova 19 (70%) were penetrated by spermatozoa and 40/54 (74%) inseminated ova transferred surgically to the oviducts of a synchronized heifer were recovered by non-surgical flushing of the uterine horns 6 days later. Of the 40 ova 15 (38%) were at the morula, early blastocyst or diminutive morula stages. Culture in vitro sustained further development of all embryos and 9 were expanding or expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…The oocytes used for this study were prepared by the method described by Xu et al (1987) (King et al, 1979).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oocytes used for this study were prepared by the method described by Xu et al (1987) (King et al, 1979).…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been noted that there is a progressive elimination of embryos with abnormal karyotype throughout early stages of development (King, 1990). Furthermore, not all fertilized oocytes are capable of completing even the first cleavage division (Xu et al, 1987 (Diskin and Sreenan, 1980 …”
Section: Methodsmentioning
confidence: 99%
“…From the onset it must be emphasized that in vitro maturation, by and large, yields oocytes with a lowered potential for developmental capacity in comparison to in vivo matured oocytes (LeibfriedRutledge et al, 1986a(LeibfriedRutledge et al, , 1987Pavlok et al, 1988 (Leibfried and First, 1979;Fukui and Sakuma, 1980;Grimes and Ireland, 1986) or even to be fertilized in vitro (LeibfriedRutledge et al, 1985). Recent (Crozet et al, 1986;Crozet, 1989 This concept has recently been substantiated by Tan and Lu (1990 (Leibfried and First, 1979;Fukui and Sakuma, 1980;Greve et al, 1984;Hensleigh and Hunter, 1985;Xu et al, 1987;Shioya et al, 1988;Greve et al, 1989b;Sirard, 1989;Younis et al, 1989;Kruip et al, 1990;Gordon and Lu, 1990; (Xu et al, 1986a).…”
Section: Cumulus Oocyte Complexesmentioning
confidence: 96%
“…In a recent study no beneficial effect of the addition of hormones was observed with regard to subsequent embryo development ). In our laboratory and many others, addition of hormones has been substituted by estrous cow serum (ECS), which has proven to be very efficient for attaining oocytes with high developmental competence (Lu et al, 1987(Lu et al, , 1988Xu et al, 1987;Fukui andOno, 1988, 1989;Lu et al, 1989;Fukui et al, 1989 (Sirard, 1990 (Osborn and Moor, 1982;Moor and Seamark, 1986). Supplementation of maturation media with additional granulosa cells has been performed in a number of studies and has been found to be absolutely essential for achieving full developmental competence (Staigmiller and Moor, 1984;Critser et al, 1986;Lu et al, 1987;Lutterbach et al, 1987;Fukui and Ono, 1988;Fukui et al, 1988;Leibfried-Rutledge et al, 1989).…”
Section: Cumulus Oocyte Complexesmentioning
confidence: 99%
See 1 more Smart Citation